Development of Islamic Boarding School Financing Management Based on Economic Independence - Yosep Farhan Dafik Sahal; Ajid Thohir; Aep Saepuloh; Hariman Surya Siregar; Zohaib Hassan Sain (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study is motivated by the challenge of economic independence for Islamic boarding schools amid the transformation of their role in the modern era. Islamic boarding schools no longer function solely as traditional Islamic educational institutions, but have also developed as centers for economic and social empowerment of the community. However, dependence on uncertain external funding sources has prompted the need to develop a sustainable economic ecosystem for Islamic boarding schools in order to strengthen the independence of these institutions. This study aims to explore the development of Islamic boarding school financing management based on economic independence. This study uses a qualitative approach, with an exploratory sequential mixed methods design. The research method uses Research and Development (R&D) with the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model. The results of the study found that: 1) Financial management in two Islamic boarding schools has been carried out systematically through planning, funding diversification, governance, and continuous evaluation with a contextual approach. 2) The development of financial management has shifted from an administrative function to an economic independence strategy based on the integration of modern governance and Islamic boarding school values.